Meta-analysis of outcomes of patients with COVID-19 infection with versus without gastrointestinal symptoms. Issue 3 (2nd July 2020) - Gul, Fahad; Lo, Kevin Bryan; Peterson, Julie; McCullough, Peter A.; Goyal, Abhinav; Rangaswami, Janani
Abstract: This systematic review analyzed whether the presence or absence of gastrointestinal symptoms in patients with SARS-COV-2 infection is associated with adverse outcomes. Searching the Cochrane Center Register of Controlled Trials, we included any studies looking at patients with COVID-19 with gastrointestinal symptoms (nausea, vomiting, diarrhea, abdominal pain) compared to those with COVID-19 but without gastrointestinal manifestations as a control group. The final search yielded 186 articles, all of which were individually screened. Seven studies were identified but three were excluded: one due to lack of a control group without gastrointestinal symptoms, one reported as viral RNA in the stool, and one with only non-critically ill patients. Results of the meta-analysis showed a pooled odds ratio for mortality among those with COVID-19 and gastrointestinal symptoms of 0.91 (confidence interval 0.49–1.68) with heterogeneity of 0% and a pooled odds ratio for acute respiratory distress syndrome of 2.94 (confidence interval 1.17–7.40) with heterogeneity of 0%. In conclusion, gastrointestinal symptoms with COVID-19 are associated with a higher risk of acute respiratory distress syndrome, but do not increase the risk for mortality.